Experimental Investigation on Influence of Molding Methods on Properties of Pervious Concrete. Issue 1 (January 2022) - Li, Qiuxiang; Zheng, Jie; Fu, Mingfu
Abstract: Despite the common use of pervious concrete (PC), there is no standard way of producing the test specimens, which undergo testing to infer the behaviour of PC in the field. Vibrating table is the most common method but greatly reduced in vibration time compare with normal concrete in the laboratory. Marshall compaction and superpave gyratory compactor (SGC) are recommended standard molding methods for porous asphalt mixtures manufactured in the laboratory environment. Three kinds of pervious concrete samples with three target porosities were prepared by the above three methods, and the effects of the molding method on the physical properties, mechanical properties and durability of the samples were investigated in the study. Experimental results showed, with different molding methods adopting, pervious concrete with the same mixture design exhibits slightly different physical and mechanical properties. After analysis and comparison, SGC is the best choice to obtain concrete with high permeability, good freeze-thaw resistance and high strength, followed by Marshall compaction molding, and vibration molding is the last one. As a result, a win-win situation of the hydraulic characteristics and mechanical properties of pervious concrete can be achieved due to both optimized mix-design and appropriate molding method.